2018
DOI: 10.1007/s00259-018-4067-3
|View full text |Cite
|
Sign up to set email alerts
|

68Ga-PSMA PET/CT in patients with recurrent prostate cancer after radical treatment: prospective results in 314 patients

Abstract: We confirmed the value of Ga-PSMA PET/CT in restaging PCa patients with BCR, highlighting its superior performance and safety compared with choline PET/CT. Higher PSApet was associated with a higher relapse detection rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
47
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(54 citation statements)
references
References 45 publications
5
47
0
2
Order By: Relevance
“…In 5 out 8 articles with available information on PSAdt, an increase of the DR of PSMA‐PET in patients with PSAdt ≤6 months and a decrease of DR of PSMA‐PET in patients with PSAdt > 6 months were reported . Of the remaining 3 articles, one study showed an opposite trend and the other two a reduction or a raise of the DR irrespective of the value of the PSAdt. The possible correlation between the DR of PSMA‐PET and PSAvel was evaluated in seven studies .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In 5 out 8 articles with available information on PSAdt, an increase of the DR of PSMA‐PET in patients with PSAdt ≤6 months and a decrease of DR of PSMA‐PET in patients with PSAdt > 6 months were reported . Of the remaining 3 articles, one study showed an opposite trend and the other two a reduction or a raise of the DR irrespective of the value of the PSAdt. The possible correlation between the DR of PSMA‐PET and PSAvel was evaluated in seven studies .…”
Section: Resultsmentioning
confidence: 99%
“…After reviewing the full texts, four articles were excluded from the quantitative analysis (meta‐analysis) due to insufficient data to reassess the correlation between PSA kinetics and DR of PSMA‐PET and 8 studies including about 1,400 patients were finally selected for the meta‐analysis (Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…PSMA PET/CT nowadays represents the molecular imaging with the highest accuracy in staging and restaging PCa patients . Several studies showed the better diagnostic performance of PSMA PET/CT as compared with other PET tracers and conventional imaging techniques (including CT, MRI and BS), even in the presence of low PSA levels . Of note, the conventional clinical practice in PCa patients with BCR after RP includes mainly three approaches (radiotherapy, ADT or observation), according to the presumed site of recurrence (local vs systemic) .…”
Section: Introductionmentioning
confidence: 99%